2015
DOI: 10.1177/0961203315591027
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hydroxychloroquine on preterm delivery and intrauterine growth restriction in pregnant women with systemic lupus erythematosus: a descriptive cohort study

Abstract: HCQ reduces neonatal morbidity in women with SLE by significantly decreasing the rate of prematurity and intrauterine growth restriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 42 publications
(62 reference statements)
3
98
2
5
Order By: Relevance
“…Given its known safety profile in pregnancy [80,109], and the acknowledged risk to both mother and fetus associated with heightened lupus disease activity in pregnancy, discontinuing HCQ during pregnancy is not advised. Indeed, several studies have suggested that HCQ therapy in SLE improves birth outcomes: in a study of 118 lupus pregnancies in which 41 women were treated with HCQ and compared to 77 SLE women who were not taking HCQ, significantly lower rates of preterm delivery (15.8% vs 44.2%; p= 0.006) and IUGR (10.5% vs 28.6%; p=0.03) were observed in the group taking HCQ [29]. In another retrospective study of outcomes of lupus pregnancies, 56 women who took HCQ through their pregnancies were compared with 163 who took no HCQ, and 38 who stopped HCQ either three months prior to conception or during their first trimesters out of concern for medication exposure to the baby [30].…”
Section: Medications During Autoimmune Ctd Pregnanciesmentioning
confidence: 99%
“…Given its known safety profile in pregnancy [80,109], and the acknowledged risk to both mother and fetus associated with heightened lupus disease activity in pregnancy, discontinuing HCQ during pregnancy is not advised. Indeed, several studies have suggested that HCQ therapy in SLE improves birth outcomes: in a study of 118 lupus pregnancies in which 41 women were treated with HCQ and compared to 77 SLE women who were not taking HCQ, significantly lower rates of preterm delivery (15.8% vs 44.2%; p= 0.006) and IUGR (10.5% vs 28.6%; p=0.03) were observed in the group taking HCQ [29]. In another retrospective study of outcomes of lupus pregnancies, 56 women who took HCQ through their pregnancies were compared with 163 who took no HCQ, and 38 who stopped HCQ either three months prior to conception or during their first trimesters out of concern for medication exposure to the baby [30].…”
Section: Medications During Autoimmune Ctd Pregnanciesmentioning
confidence: 99%
“…Active/flaring SLE at conception or in the 4e6 months before has also been associated with adverse pregnancy outcomes (APO) other than EPL: late pregnancy losses (LPL), neonatal death, preterm delivery/prematurity, hypertensive complications and probably intrauterine growth restriction (IUGR) and small for gestational age (SGA) newborns [16,22e27]. Even though the disease could be in remission at the time of conception, major organ involvements such as renal or neurological, should be considered as risk factors for APO [13,21,28,29].…”
Section: Maternal and Foetal Outcome In Sle Pregnancymentioning
confidence: 99%
“…HCQ use during pregnancy prior to 2000 was not common practice, but increasing reports of its safety and efficacy during pregnancy have since changed prescribing patterns. [18] In our study, HCQ use either prior or during pregnancy was not related to pregnancy outcome, nor was year of conception (pre- vs. post-2006).…”
Section: Discussionmentioning
confidence: 52%